Evaluation of hearing screening in newborns in Poland - Lidia Bubula; Nicol Dardzińska; Karolina Dorobisz (Pediatria Polska, 2022)
The Universal Newborn Hearing Screening Program (UNHSP), which has been in operation in Poland since 2002, enables the use of modern, impartial techniques in detecting congenital hearing impairment. It is free and generally available, and so it gains high attendance. The examination uses globally accepted methods of hearing screening: Otoacoustic Emission and Auditory Brainstem Response. The first examination takes place on the obstetric or neonatal ward and allows the examiner to discover any hearing impairment at an early stage. It is important in the context of psychosomatic development of the children. Special attention is paid to newborns with inherited risk factors of hearing impairment. It turns out that < 10% of examined newborns are referred for a check-up in a higher reference centre, and only < 1% of examined children have actual hearing impairment. This review article presents an evaluation of the UNHSP in Poland.